Explicit and indirect, latency-based measure of aggression in striking combat sports - Predoiu, Radu; Piotrowski, Andrzej; Stan, Elena Amelia; Ciolacu, Mihai Valentin; Bitang, Andrei; Croitoru, Doina; Cosma, Germina (Frontiers in Psychology, 2024)
Introduction: Aggression in sports is often perceived as a necessary trait for success, especially in martial arts. Aggression can be assessed both explicitly and implicitly, taking into account the dual processing model. The purpose of the research is to examine explicit and indirect, latencybased measure of aggression in competitive athletes practicing striking combat sports, according to gender and sports performance. At the same time, we verified if aggression (implicit/unconscious and explicit) predicts sports performance in martial artists. Materials and methods: 85 athletes practicing striking combat sports took part in the research. For implicit, latency-based measure of aggression an Implicit Associations Test (IAT) was used, while explicit aggression was assessed with The Romanian adaptation of the Makarowski's Aggression Questionnaire for martial arts athletes. Results: Data analysis revealed (using multivariate analysis of variance), that athletes from striking combat sports having international sports performances registered significantly higher D-scores (IAT, p = 0.014), and lower values for Goahead factor (p = 0.006), compared to athletes without outstanding results. Goodman and Kruskal tau association test was used to check the existing associations between athletes' gender and martial arts athletes' level of explicit and implicit aggression. Also, binomial logistic regression procedures were performed, predicting martial artists' likelihood to obtain higher sports results, based on explicit and indirect aggression. Conclusion: A stronger association between Aggression and Others (at implicit/ unconscious level), and a moderate level (generally) for Go-ahead factor of explicit aggression, are associated with an increased likelihood of sports performances in athletes. Also, male martial arts athletes are more persistent despite obstacles, remaining more on the offensive (no gender-related association were found in terms of indirect/unconscious aggression, and for Foul Play and Assertiveness factors of explicit aggression). The study underlines the importance of addressing athletes' subconscious level to promote more constructive behaviors in competitions.1.